Fruit and Vegetable Intake in Adolescents: Association with Socioeconomic Status and Exposure to Supermarkets and Fast Food Outlets - Chalida M. Svastisalee; Bjørn E. Holstein; Pernille Due (Journal of Nutrition and Metabolism)
Background. We investigated differences in family social class associations between food outlet exposure and fruit and vegetable intake. Methods. We supplemented data from the 2006 Health Behavior in School Aged Children Study (n=6,096) with geocoded food outlet information surrounding schools (n=80). We used multilevel logistic regression to examine associations between infrequent fruit and vegetable intake and supermarket and fast food outlet concentration, stratified by family social class. Results. Boys and older children were most likely to eat fruit and vegetables infrequently. High fast food outlet exposure was marginally significant for low fruit intake in low social class children only. Children from middle and low social class backgrounds attending schools with combined high fast food outlet/low supermarket exposure were most likely to report infrequent fruit intake (ORlow=1.60; CI:  1.02–2.45; ORmid=1.40; CI:  1.03–190). Children from low social class backgrounds were also likely to report infrequent vegetable intake, given low supermarket and high fast food outlet exposure (OR=1.79; CI:  0.99–3.21). Conclusion. Our findings suggest social class modifies the relationship between intake and food outlet concentration. School interventions improving fruit and vegetable intake should consider neighborhood surroundings, targetting older children from low social class backgrounds.